(untitled) (Nativa, 2024)
A densidade básica da madeira possui grande importância no controle de qualidade da madeira, devido a fácil determinação e alta correlação com as demais características da madeira, porém esta possui grande variabilidade no sentido longitudinal do tronco. Neste contexto, este trabalho teve como objetivo analisar possíveis otimizações de pontos amostrais ao longo do fuste para a determinação da densidade básica da madeira de Eucalyptus saligna. As árvores foram amostradas em 0%, diâmetro na altura do peito (DAP), 33%, 66% e 100% da altura comercial. A partir da densidade básica pontual foram definidas a densidade média ponderada pelo volume e a densidade média aritmética da árvore. Os resultados demonstraram que não se pode assumir que a densidade média aritmética equivale ao valor da densidade média ponderada pelo volume da madeira de Eucalyptus saligna. Não foi possível determinar um único ponto ótimo de amostragem, ressaltando ainda que a amostragem na altura referente ao DAP não é indicada. Utilizando-se da combinação de dois pontos amostrais, as posições DAP e 33% apresentaram melhor estimativa da densidade básica. Já com três pontos amostrais, a estimativa da densidade básica pode ser obtida com alta precisão, se a amostragem for realizada nas posições DAP, 33% e 66%. Palavras-chave: qualidade da madeira; massa específica básica; variação longitudinal. Sampling points optimization along the stem to determine the wood basic density of Eucalyptus saligna ABSTRACT: The wood basic density is important for wood quality control, because it is easy to determine and has high correlation with other wood characteristics, however, basic density has wide variability even in the same tree, mainly along stem longitudinal direction. In this context, this study objective was to analyze different possibilities to sampling points optimization along the stem to determine the wood basic density of Eucalyptus saligna. At the trees were sampled at heights for 0%, diameter at breast height (DBH), 33%, 66% and 100% commercial height. From punctual basic density, average density weighted by volume and arithmetic average density of each tree were defined. The results showed that it is not possible to assumed with statistical certainty that the arithmetic average density accurately estimates the value of Eucalyptus saligna wood weighted average density. Determine a single optimal sampling point was not possible, it is worth mentioning that sampling only at height referring to DBH is not indicated. Using two sample points combination, DBH and 33% positions presented wood basic density best estimate. With three sampling points, density estimate can be obtained with high precision, if sampling is performed in DBH, 33% e 66% positions. Keywords: wood quality; specific gravity; longitudinal variation.